STUDI PERBANDINGAN EKONOMI REGIONAL KALIMANTAN TIMUR DAN RIAU - Mubyarto Mubyarto (Populasi, 1991)
A financially constrained central goverment no longer has the capacity to fund major development projects throughout the country. Jakarta must look more to the regions for ideas,money and initiatives.Reforms are required in regional authority, and innational programmes-from rice to foods policies and transmigration-which have a regional impact. The "unity" of the last twenty years of strong central government has to be complemented more effetively by the "diversity" which flows from a greater emphasis inregional initiative and self reliance.